2021
DOI: 10.3390/nu13051682
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Analysis of Gut and Skin Microbiota in Infants with Food Allergy and Atopic Dermatitis: A Pilot Study

Abstract: The gut microbiota in patients with food allergy, and the skin microbiota in atopic dermatitis patients differ from those of healthy people. We hypothesize that relationships may exist between gut and skin microbiota in patients with allergies. The aim of this study was to determine the possible relationship between gut and skin microbiota in patients with allergies, hence simultaneous analysis of the two compartments of microbiota was performed in infants with and without allergic symptoms. Fifty-nine infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 81 publications
3
23
0
1
Order By: Relevance
“…The strengths and limitations of our study group were described earlier [28]. Additional strengths stem from the inclusion of milk; this is the first study analyzing the microbiomes of milk, skin and feces simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The strengths and limitations of our study group were described earlier [28]. Additional strengths stem from the inclusion of milk; this is the first study analyzing the microbiomes of milk, skin and feces simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…The study group was described in detail earlier [28]. A diagram depicting the steps of patients' enrollment and the samples collected in this study is shown in Figure 1.…”
Section: Study Groupmentioning
confidence: 99%
See 3 more Smart Citations